Pengembangan E-LKPD Berbasis Inkuiri Terbimbing untuk Meningkatkan Keterampilan Proses Sains Siswa SMP - Galih Dian Masruhah; Rusdianto Rusdianto; Sri Wahyuni (SAP (Susunan Artikel Pendidikan), 2022)
One of the worksheets that can improve process skills is the guided inquiry-based worksheets. However, the LKPD is still in printed form so it is less effective to use during pandemic. Therefore, it is necessary to develop guided inquiry-based worksheets in electronic form. One of the websites that provide this service is liveworksheet. This study aims to examine the validity, practicality and effectiveness of guided inquiry-based e-worksheets to improve the science process skills of junior high school students in science learning. This research method was R&D with the ADDIE development model (analyze, design, develop, implement and evaluate). The developed e-worksheets was piloted on class VIII-F students at SMP Negeri 1 Wuluhan in the even semester of the 2021/2022 academic year. The results showed that the guided inquiry-based e-worksheets developed was valid with a percentage of 91%, very practical with a percentage of 87.03% and quite effective with an N-gain value of 0.62.